How does China fare on the Russian market? - García Herrero, Alicia,Xu, Jianwei (Bruegel, 2019)
China's economic ties with Russia are deepening, particularly in terms of trade and cross-border lending, but less so in terms of Chinese foreign direct investment in, or portfolio flows to, Russia. Meanwhile, Europe remains Russia's largest trading partner, lender and investor. In relation to trade, an analysis of China's increasing export share and the increasing value added of its exports, and previous empirical analysis at the product level, indicate that China seems to have become more of a competitor to the European Union on Russia's market. Increasing competition between European and Chinese exports should not be surprising as there is ample evidence that China has rapidly moved up the technology ladder in the last few decades. Competition over investment and lending is more limited, but the situation could change rapidly with China and Russia giving clear signs of a stronger than ever strategic partnership.
10419/237607
Keywords: Graue Literatur; Wirtschaftsbeziehungen; Außenhandel; Marktzugang; Export; Internationale Kapitalbewegung; Direktinvestition; Wertschöpfungskette; Marktmacht; Implikation; Mitgliedsstaaten; Internationaler Wettbewerb; Entwicklung; Tendenz